Zinc Electrowinning Using Reactive Electrodialysis (Red) - Cifuentes-Molina, G; Bustos-Cerda, P (Sociedad Chilena de Quimica, 2014)
This paper presents an alternative process for the conventional zinc electrowinning, which consists of a cell of two compartments separated by a anion exchange membrane. One of them contains a zinc sulphate catholyte and sulfuric acid while the anolyte solution contains ferrous sulfate and sulfuric acid. By using a membrane the classical lead anode may be replaced, as well as the main oxidation reaction of water, for that of the ferrous ion to ferric ion. This leads to significant savings in specific energy consumption of the overall process and eliminates the classic problem of acid mist in electrowinning cells. The results show that the proposed process consumes 30% less cell potential compared to conventional electrowinning cell. © 2014, Sociedad Chilena de Quimica. All rights reserved.